Almost Projective Semimodules - Khitam Sahib Aljebory; Asaad Mohammed Ali Alhossaini (مجلة بغداد للعلوم)
The basis of this paper is to study the concept of almost projective semimodules as a generalization of projective semimodules. Some of its characteristics have been discussed, as well as some results have been generalized from projective semimodules.